Find the root by factrisation2x^2-x+1/8=0
Answers
Answered by
1
Greetings,
The answer to your question is typed below ^
______________________________________________________________
Given:
2x² - x + 1/8 = 0
Solution:
First we multiply each term by 8 to make calculations easier.
we get:
(2x²)8 - (x)8 + (1/8)8 = 0
⇒ 16x² - 8x + 1=0
⇒ 16x² - 4x - 4x + 1 = 0 ( by splitting the middle term -8x as -4x and -4x)
⇒ 4x(4x - 1) - 1 ( 4x - 1) = 0 ( here take 4x and -1 common)
⇒ (4x - 1) (4x - 1)=0
⇒ x = 1/4 or x = 1/4
Ans.: x = 1/4 or 0.25
____________________________________________________________
We can also use the b²-4ac method:
we take the equation 16x² - 8x +1 =0
Then take the coefficients of x², x and the last term
as
a = 16 , b = -8 , c = 1
according to the formula x = (-b +/- √(b² - 4 a c)) / 2a
∴ x = ( 8 +/- √ (64 - 4 * 16 * 1)) / 2 * 16
⇒ x= ( 8 +/- √(64 -64) ) / 32
⇒ x = ( 8 +/- 0) / 32
x= ( 8 + 0 ) /32 or x= ( 8 - 0 ) / 32
x = 1/4 or x = 1/4
_____________________________________________________________
PS.: Enjoy ;)
The answer to your question is typed below ^
______________________________________________________________
Given:
2x² - x + 1/8 = 0
Solution:
First we multiply each term by 8 to make calculations easier.
we get:
(2x²)8 - (x)8 + (1/8)8 = 0
⇒ 16x² - 8x + 1=0
⇒ 16x² - 4x - 4x + 1 = 0 ( by splitting the middle term -8x as -4x and -4x)
⇒ 4x(4x - 1) - 1 ( 4x - 1) = 0 ( here take 4x and -1 common)
⇒ (4x - 1) (4x - 1)=0
⇒ x = 1/4 or x = 1/4
Ans.: x = 1/4 or 0.25
____________________________________________________________
We can also use the b²-4ac method:
we take the equation 16x² - 8x +1 =0
Then take the coefficients of x², x and the last term
as
a = 16 , b = -8 , c = 1
according to the formula x = (-b +/- √(b² - 4 a c)) / 2a
∴ x = ( 8 +/- √ (64 - 4 * 16 * 1)) / 2 * 16
⇒ x= ( 8 +/- √(64 -64) ) / 32
⇒ x = ( 8 +/- 0) / 32
x= ( 8 + 0 ) /32 or x= ( 8 - 0 ) / 32
x = 1/4 or x = 1/4
_____________________________________________________________
PS.: Enjoy ;)
Similar questions